Epidemiological study of risk factors of stroke and its immediate consequence - Haque, MM; Nasreen, SA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):124-8.The abstract of this article is available on the PubMed website